Performance of Vertical Flow Systems for Passive Treatment of Acid Mine Drainage (The Australasian Institute of Mining and Metallurgy, 2003)
Vertical flow systems (SAPS, vertical flow wetlands) are increasingly used for passive treatment of mine drainage that is net acid. Data on 30 systems in eastern US show that well designed systems typically add about 40 g/d/m2 of alkalinity to influent net acid water. If they are designed with a conservative loading rate of 25 g/d/m2 and carefully constructed, they produce net alkaline water. Alkalinity added depends on influent acidity, Fe, pH, and retention time, and ranges widely, from 7 to 484 mg/L, so this is not a useful design criterion. Some waters may benefit from retention times longer than the conventional 12 - 16 hours, but the design must be partly based on cost-benefit considerations. Systems with fine limestone added to the compost layer perform better than average, perhaps to an alkalinity generation rate of 80 g/m2/d. A variety of problems are noted in the 30 systems and others reported in the literature. Systems with high influent Fe (> ~75 mg/L, varying with pH) tend to gradually decrease in flow rate because of precipitation and settling of Fe hydroxides on top of the compost layer. Some high-Fe systems precipitate Fe in the limestone layer, suggesting inadequate compost thickness, or short-circuiting through thin spots. Systems with Al exceeding about 10 mg/L tend to plug because of Al hydroxide precipitation in the limestone layer. Flushing only removes a small part of this precipitate, but can extend life. Some systems are ineffective because of failure of the inflow system. Some systems are uneconomic because they are oversized. A continuing program of inspection and maintenance is necessary for long-term performance.